Aerospace series. Steel X4CrNiMo16-5-1 (1.4418). Air melted. Hardened and tempered. Forgings. De ≤ 200 mm. 1 150 MPa ≤ Rm ≤ 1 300 MPa. (20th January 2023) - British Standards Institution,
No abstract available